Analyse des facteurs influençant la Croissance des Plantes : Étude et Modélisation - KHAOUID, Taqiyeddine (My University, 2025)
This thesis focuses on analyzing the effects of different fertilization types on the growth of two crops: wheat and sunflower. The study is based on agronomic data collected under real conditions, including three key climatic variables: temperature, relative humidity, and wind speed. An initial descriptive analysis was conducted to identify general growth trends for each plant according to the applied treatments. This was followed by an analysis of variance (ANOVA) to determine the significance of differences observed between fertilization types. Finally, multiple linear regression was performed to model plant height as a function of climatic variables, allowing for an assessment of the combined influence of these environmental factors. The results provide insights into the effectiveness of the tested fertilizers and highlight the interactions between climatic conditions and plant development, thus contributing to a better understanding of cultivation practices suited to the two studied species.
Keywords: Crop modeling; Plant growth; Climatic factors; Descriptive analysis; ANOVA; Multiple linear regression; Agronomic data; Agricultural practices